Ticagrelor Improves Endothelial Function by Decreasing Circulating Epidermal Growth Factor (EGF) - Vieceli Dalla Sega, Francesco; Fortini, Francesca; Aquila, Giorgio; Pavasini, Rita; Biscaglia, Simone; Bernucci, Davide; Del Franco, Annamaria; Tonet, Elisabetta; Rizzo, Paola; Ferrari, Roberto; Campo, Gianluca (Frontiers in Physiology, 2018)
Ticagrelor is one of the most powerful P2Y12 inhibitor. We have recently reported that, in patients with concomitant Stable Coronary Artery Disease (SCAD) and Chronic Obstructive Pulmonary Disease (COPD) undergoing percutaneous coronary intervention (PCI), treatment with ticagrelor, as compared to clopidogrel, is associated with an improvement of the endothelial function (Clinical Trial NCT02519608). In the present study, we showed that, in the same population, after one month treatment with ticagrelor, but not with clopidogrel, there is a decrease of the circulating levels of epidermal growth factor (EGF and that these changes in circulating levels of EGF correlate with on-treatment platelet reactivity. Furthermore, in human umbilical vein endothelial cells (HUVEC) incubated with sera of the patients treated with ticagrelor, but not with clopidogrel there is an increase of p-eNOS levels. Finally, analyzing the changes in EGF and p-eNOS levels after treatment, we observed an inverse correlation between p-eNOS and EGF changes only in the ticagrelor group. Causality between EGF and eNOS activation was assessed in vitro in HUVEC where we showed that EGF decreases eNOS activity in a dose dependent manner. Taken together our data indicate that ticagrelor improves endothelial function by lowering circulating EGF that results in the activation of eNOS in the vascular endothelium.